Abortion, sin, and the state in Thailand - Whittaker, Andrea (Andrea M.), 1967- (ASAA women in Asia series., 2004)
This book discusses abortion in a non-Western, non-Christian context - in Thailand, where over 200,000 to 300,000 illegal abortions are performed each year by a variety of methods.